Kinematic and temporal analysis of overarm throwing in Finnish baseball players under different instructions - Alway, Peter (2016)
The velocity-accuracy trade-off in overarm throwing has been well studied, but has presented conflicting results. The cause of the velocity-accuracy trade-off is poorly understood. The present study therefore aimed: to determine if a velocity-accuracy trade-off exists in Finnish baseball players, and to determine if there was any difference in kinematics, timing of movements, and intra-subject movement variability between three different throwing instructions. Eight elite Finnish baseball players (mean age = 25.00yr, mean height = 1.82m, mean body mass = 86.65kg) threw 10 times in accuracy, velocity and combination instructions towards a 0.07m target, from a distance of 20m. A 3-D motion analysis system measured ball velocity and kinematics. Relative ball velocity significantly differed between groups (84.15%, 96.69% and 91.01% of maximum ball velocity, in accuracy, velocity and combination instructions respectively), while no significant differences were observed between groups in accuracy scores (total error = 52.18cm, 60.18cm and 54.54cm in accuracy, velocity and combination instructions respectively). A velocity-accuracy trade-off was not present, attributed to the demands of the sport, and the skill level of the participants. A trade-off between velocity and the task prioritization of accuracy was present. Great ball velocity when emphasizing accuracy questions the application of the velocity-accuracy trade-off in elite sports. No significant difference in movement variability and timing of maximum joint rotations between instructions suggests that technique is consistent across near-maximum and maximum throws. Further, this result suggests that the impulse-variability theory is too simplistic for complex multijoint movements. Multiple significant differences in kinematics were observed between instructions, suggesting that in greater velocity throws, concentric contractions of the shoulder are facilitated by increased use of the stretch shortening cycle.